Effect of glucagon-like peptide-1 receptor agonists and sodium-glucose cotransporter-2 inhibitors on time to outcome in type 2 diabetes cardiorenal outcome trials - Rizzi, Alessandro; Kloecker, David E.; Pitocco, Dario; Khunti, Kamlesh; Davies, Melanie J.; Zaccardi, Francesco (Diabetes & metabolic syndrome clinical research & reviews, 2024)
In randomized controlled trials (RCTs), treatment effects are commonly reported as hazard ratio, a measure often misinterpreted as a relative risk reduction. The acceleration factor (AF) indicates the extent to which a treatment increases/decreases the time before the occurrence of an outcome and gives useful insights in the interpretation of trials’ results. Using individual time-to-event data reconstructed from Kaplan-Meier plots, we estimated AFs for the primary outcomes (POs) and all-cause mortality in glucagon-like peptide-1 receptor agonists (GLP1-RAs) or sodium-glucose cotransporter-2 inhibitors (SGLT2-is) cardiorenal outcome trials in subjects with type 2 diabetes. AFs were estimated from 28 Kaplan-Meier plots of 19 RCTs. Compared to placebo, most GLP1-RAs increased the time before the onset of POs (from 9 % to 59 %) and all-cause mortality (from 8 to 13 %). Similarly, SGLT2-is increased time before the onset of POs (from 19 % to 87 %) and all-cause mortality (from 13 % to 42 %). The AFs provide a complementary and easier-to-interpret measure of treatment effect that could be useful to improve the shared decision-making. •The acceleration factor (AF) – how the time before an outcome is increased/decreased – can help interpret trial's result.•Using reconstructed time-to-event data, we estimated AFs for primary outcomes and death in GLP1-RAs and SGLT2-is trials.•AFs provide an easy-to-interpret measure of treatment effect, adding actionable information in clinical decision-making. SUMMARY In a randomised controlled trial, the acceleration factor (AF) indicates the extent to which the occurrence of an outcome is accelerated or delayed by an intervention, providing a complementary, easy-to-interpret measure of treatment effect. We estimated AFs for primary outcomes and all-cause mortality in type 2 diabetes cardiorenal outcome trials.